Effects on Somali-Arabian goat doe body weight, birth weight and hay intake of rations of varying digestible energy fed during pregnancy - Hassan, H.M. (1989)
Productivity of Somali goats is generally low due to poor husbandry practices. The effects of nutrition on birth weight, body weight and hay intake of does fed diets varying in digestible energy during the last 4 months of pregnancy were studied on 24 Somali-Arabian goats. Body weight of pregnant goats and kid birth weight increased with the level of digestible energy. Hay and total feed intake tended to decrease as digestible energy in the concentrate increased and also as goats approached parturition. None of these increases were significant. A low digestible energy level (29.3 Mcal/kg) in the concentrate is adequate for daily digestible energy requirements of Somali-Arabian goats during the last 6 week of pregnancy.